Plasma pharmacokinetics tissue concentration and urine elimination after cephalotin intravenous administration to cats under surgical conditions - Albarellos, Gabriela Alejandra (2015)
Pharmacokinetic profile, tissue concentrations and urine elimination of cephalothin in cats under surgical conditions after a single intravenous dose (30 mg/kg) were studied. Initial plasma concentrations were high (Cp(0), 353.79±118.92 μg/mL), with fast and moderately wide distribution (T1⁄2(d) 0.14±0.10 h) (V(d(ss)) 0.19±0.03 L/kg) and rapid elimination (ClB, 0.16±0.03 L/h.kg; T1⁄2, 1.07±0.23 h; MRT, 1.16±0.21 h). Thirty to 60 minutes after intravenous administration, cephalothin tissue concentrations were in the range of 3.73 μg/g (testicle tissue) to 25.63 μg/g (uterus). Tissue/plasma concentrations rate was in a range of 0.04 (testicle) to 0.21 (uterus). Cephalothin urine elimination was 66.49% in the first 6 hours after administration. Cephalothin plasma concentrations remained above a MIC≥1μg/mL up to 5.5 hours in all the studied cats. However, for MIC≥8μg/mL (MIC breakpoint) this time is reduced to 2.5 hours. This suggests that proper perioperative prophylactic use of cephalothin in cats requires a dose interval not longer than 2 hours.